Anti‐NMDAR encephalitis: case report and diagnostic issues. Issue 1 (8th September 2014) - Omura, Taishi; Sonoda, Seijiro; Nagata, Katsuhiro; Okita, Taihei; Hoshiai, Akira; Sano, Hidefumi; Tanaka, Yosuke; Tsurukiri, Junya; Arai, Takao; Ohta, Shoichi
Abstract : Case: A 20‐year‐old woman developed acute psychotic symptoms and altered level of consciousness. She presented with neck stiffness, tremulous arms, facial dyskinesia, and distension of the lower abdomen. Pelvic magnetic resonance imaging showed bilateral ovarian teratomas. Anti‐N‐methyl‐D‐aspartate receptor antibodies were detected in her cerebrospinal fluid. Outcome: Resection of the tumors and immunotherapy were carried out. She gradually recovered and was discharged with few neurological deficits on the 105th day of hospitalization. Conclusion: Our survey of 63 previous reports describing 92 cases revealed that 21.7% of the patients were sent to emergency departments and 59.8% of the patients were managed in intensive care units. Emergency physicians and intensivists should be aware of this disorder, as they may encounter undiagnosed disorders in patients with epileptic attacks, acute psychotic signs, dyskinesia, or hypoventilation in the course of the illness.